2017
DOI: 10.1155/2017/4780746
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of the Ethanol Extract from Flos Rosae Chinensis with Activity against Fluconazole‐Resistant Clinical Candida

Abstract: This study was designed to investigate the antifungal activity of a hydroalcoholic extract from Flos Rosae Chinensis (FRC) combined with fluconazole (FCZ) against clinical isolates of Candida albicans resistant to FCZ. The minimum inhibitory concentration (MIC) of FRC was determined using a checkerboard microdilution assay. The synergistic effects of the combination of FRC and FCZ against clinical isolates of C. albicans resistant to FCZ were further confirmed by constructing time-growth curves and performing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“… 20 Many plant-derived substances have shown their effectiveness to fight Candida infections, particularly those less susceptible to current antifungal drugs. 45 The use of alcoholic extract of Flos rosae chinensis has been shown to increase the activity of FLZ against the drug-resistant C. albicans . 46 The extract of Punica granatum and its purified compound punicalagin showed a synergistic effect with FLZ.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Many plant-derived substances have shown their effectiveness to fight Candida infections, particularly those less susceptible to current antifungal drugs. 45 The use of alcoholic extract of Flos rosae chinensis has been shown to increase the activity of FLZ against the drug-resistant C. albicans . 46 The extract of Punica granatum and its purified compound punicalagin showed a synergistic effect with FLZ.…”
Section: Discussionmentioning
confidence: 99%
“…, Mahonia aquifolium Nutt. , Glycyrrhiza glabra L. and so on, were reported to exert antifungal activity [813]. In our screening study, we found that Maianthemum japonicum ( A.…”
Section: Introductionmentioning
confidence: 87%
“…For the time-kill curve experiments, 25 C. albicans ZY23 was cultured in YPD liquid medium for 16 h, and then the fungal suspension (100 μL) was transferred to fresh YPD liquid medium (10 mL). After culturing for another 4 h, the fungi were washed with PBS three times and resuspended in RPMI medium to a final concentration of 1×10 3 CFU/mL.…”
Section: Methodsmentioning
confidence: 99%